2017
DOI: 10.1186/s12885-017-3632-7
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 carriers with male breast cancer show elevated tumour methylation

Abstract: BackgroundMale breast cancer (MBC) represents a poorly characterised group of tumours, the management of which is largely based on practices established for female breast cancer. However, recent studies demonstrate biological and molecular differences likely to impact on tumour behaviour and therefore patient outcome. The aim of this study was to investigate methylation of a panel of commonly methylated breast cancer genes in familial MBCs.Methods60 tumours from 3 BRCA1 and 25 BRCA2 male mutation carriers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Although the acquisition of epigenetic alterations, in general, and aberrant DNA methylation, in particular, is widely acknowledged as an early and relevant event in tumorigenesis [29], these have been seldom reported and with different purposes, in male BC [4,[18][19][20][21]. Kornegoor et al, examined promoter methylation of 25 genes in 108 male BCs using methylation specific multiplex ligation dependent probe amplification and concluded that promoter methylation was common in male BC and that high methylation status correlated with aggressive phenotype and poor outcome [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the acquisition of epigenetic alterations, in general, and aberrant DNA methylation, in particular, is widely acknowledged as an early and relevant event in tumorigenesis [29], these have been seldom reported and with different purposes, in male BC [4,[18][19][20][21]. Kornegoor et al, examined promoter methylation of 25 genes in 108 male BCs using methylation specific multiplex ligation dependent probe amplification and concluded that promoter methylation was common in male BC and that high methylation status correlated with aggressive phenotype and poor outcome [18].…”
Section: Discussionmentioning
confidence: 99%
“…Johanssen et al performed a genome-wide methylation profiling of 47 male BC, underscoring the heterogeneity of this entity and suggesting that male BC should not be defined using conventional criteria applied to female breast cancer [20]. Using methylation-sensitive high resolution, Deb et al assessed a panel of 10 genes in 60 male BCs, concluding that BRCA2-associated male BC was characterized by high gene methylation and that the average methylation index might be a useful prognostic marker [4]. Finally, Rizzolo et al assessed promoter methylation in 69 male BC patients and concluded that alterations in methylation patterns were common in BC and might identify specific subgroups related to BRCA1/2 mutation status and some clinicopathologic parameters [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have pointed that a significant number of patients (mostly BRCA2 mutation positive) developed multiple cancers including male breast cancer; most male cancers are ER positive but without a corresponding increase in PR positivity and only a weaker association with estrogen-controlled markers such as PS2, HSP27, and Cathepsin D; increased methylation defines a subset of familial male breast cancer and with average methylation index may be a useful prognostic marker. [ 32 34 ]…”
Section: Discussionmentioning
confidence: 99%